Meaning and Social Reality of Praja IPDN: Phenomenological Studies on Meaning and Social Reality about Identity as Praja IPDN at Jatinangor - Zainal Abidin (Jurnal Politikom Indonesiana, 2018)
The purpose of this study is to know the meaning of how the meaning of praja IPDN about their social reality as praja IPDN. This research uses qualitative method with phenomenology approach that aims to know the world from the point of view of the person who experienced it directly or related to the nature of human experience, and the meaning that is attached to it. The result of the research shows that the meanings of praja IPDN on their social reality as praja IPDN are divided into four meanings, first meaning is, as the pride of the family, two are skillfull candidate leader, third is superior college and fourth is PDH as the keepeer of behavior in social interaction. Their interpretation of the symbols attached to the identity of praja IPDN as an honor, leadership, knighthood, and others also affect their actions. The significance of this symbol will be more perfect when the intensity of interaction with fellow leaders, especially their seniors, is increasing. Moreover, these symbols created and understood by these masters are symbols that bind their cohesiveness inside and outside the campus.Keywords: Phenomenology, Meaning, Social Reality, Praja IPDN.